The integration of strategy formulation and implementation in the Greater Sekhukhune District Department of Basic Education, Limpopo Province - Machabaphala, Sello Nelson (University of Limpopo (Turfloop Campus), 2010)
This research report is based on integration of strategy formulation and implementation in the Greater Sekhukhune District Department of Basic Education, Limpopo Province. The purpose of this research is to investigate the key drivers in the formulation and implementation of strategies and how can they be integrated to achieve the formulated goals and objectives of Greater Sekhukhune District Department of Basic Education. This report deals only with qualitative research method. The major findings of the study are that there are key drivers of strategy formulation and key drivers of strategy implementation and their outcomes. The key drivers of strategy formulation are the vision and mission statements, long-term objectives, and generation and selection of grand strategies; whereas the key drivers of strategy implementation are leadership, organizational culture and organizational structure .The integration of these key drivers is essential for the implementation of strategies, leading to improved service delivery to various stakeholders. The report concludes that in order to approach strategy formulation and strategy implementation in an integrated manner, the following should take place : (1) managers and staff members who are responsible for strategy implementation should also be involved in strategy formulation processes ; (2)organizational culture should be changed to create a conducive environment for the managers and the employees to be motivated to render quality services at service points ; (3) leadership and management to guide vision and mission of the district; (4) organizational structure to ‘fit’ implementation of strategies for efficiency and effectiveness of the integration of strategy formulation and implementation to achieve formulated goals and objectives.
Thesis (MBA) --University of Limpopo, 2010
Keywords: Strategy formulation; 372.1200968; Basic education -- South Africa; School management and organization -- South Africa